The Artistic Features of Omon Matjon’s Works - Shohista Saydievna, Ahmedova (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the study of the peculiarities of the lyrics of Omon Matjon and the issue of art. The article reveals the poet’s contribution to the development of Uzbek poetry of the twentieth century and the peculiarities of his poetry. Several of the poet’s poems are analyzed. Special attention is paid to the content of the poet’s series of poems “I love you.” Where appropriate, the poet’s work is evaluated on the basis of the views of literary scholars. The sincerity, simplicity, and cast lines in his poems are analyzed and interpreted.